Organization of some repetitive DNAs and B chromosomes in the grasshopper Eumastusia koebelei koebelei (Rehn, 1909) (Orthoptera, acrididae, leptysminae) - Anjos, Allison [UNESP]; Loreto, Vilma; Cabral-de-Mello, Diogo C. [UNESP] (Pensoft Publishers, 2016)
B chromosomes occur in approximately 15% of eukaryotes and are usually heterochromatic and rich in repetitive DNAs. Here we describe characteristics of a B chromosome in the grasshopper Eumastusia koebelei koebelei (Rehn, 1909) through classical cytogenetic methods and mapping of some repetitive DNAs, including multigene families, telomeric repeats and a DNA fraction enriched with repetitive DNAs obtained from DOP-PCR. Eumastusia k. koebelei presented 2n=23, X0 and, in one individual, two copies of the same variant of a B chromosome were noticed, which are associated during meiosis. The C-positive blocks were located in the pericentromeric regions of the standard complement and along the entire length of the B chromosomes. Some G+C-rich heterochromatic blocks were noticed, including conspicuous blocks in the B chromosomes. The mapping of 18S rDNA and U2 snDNA revealed only autosomal clusters, and the telomeric probe hybridized in terminal regions. Finally, the DOP-PCR probe obtained from an individual without a B chromosome revealed signals in the heterochromatic regions, including the entire length of the B chromosome. The possible intraspecific origin of the B chromosomes, due to the shared pool of repetitive DNAs between the A and B chromosomes and the possible consequences of their association are discussed.
Keywords: Cytogenetics; DOP-PCR; FISH; Multigene family; Orthoptera